The Effect Of Psycoreligius Therapy Of Listening To Yasin's Letter On Stress Level In The Elderly - Dewi Nurhanifah; Reza Herdian Fadilla; Wahyudin Wahyudin (Health Media, 2021)
The elderly are very susceptible to stress disorders because naturally they experienced a decrease in their ability to sustain life, adjust to their environment, bodily functions, and psychology naturally. Handling is done to overcome these impacts, namely encouraging activities such as religious activities, social interaction, communicating attention, group modalities and handling with drug therapy. This research aims to study psychoreligious therapy listening to Yasin letter on stress levels in the elderly at social institutions Tresna Werdha Budi Sejahtera, South Kalimantan Province. This research uses a research design “Quasi Experimental Pre-Post Test With one group” with psychoreligious therapy intervention listening to Yasin letter. The sample in this study amounted to 35 respondents using Simple Random Sampling technique. The results of the analysis with the Paired T Test get a p value of 0,000 this value is smaller than (0.05), then it can be concluded that Ho was rejected and accepted Ha which means there is a significant influence on psychoreligious therapy listening to Yasin letter on stress levels in the elderly at social institutions Tresna Werdha Budi Sejahtera, south Kalimantan Province